Eating rabbit meat and blood cannot cure asthma - Entezar Mehrabi Nasab; Seyyed Shamsadin Athari (Open Journal of Asthma - Peertechz Publications, 2021)
Asthma is a complicated chronic airway disease that characterized by structural and functional changes responsible for airway hyperresponsiveness and usually reversible airway obstruction. Allergic asthma is widely triggered by an immune-inflammatory response driven by Th2 lymphocytes and these cells contribute to the pathogenesis of asthma, thus worsening its severity. Airway hyperresponsiveness,